Is India ready for fundamental right to health? - Khanna, Vasudha; Dumka, Neha; Kotwal, Atul (International Journal Of Community Medicine And Public Health, 2024)
The right to health, a vital indicator of human development and thus, the economic and social development, has been an age-old phenomenon in India. Although, no explicit recognition to the right to health or healthcare has been given under the Indian constitution, the hon’ble supreme court, through various judicial interpretations, has repeatedly observed that right to health is a part of fundamental right to life and personal liberty enshrined under article 21. However, the fundamental policy question being raised in recent years is whether to guarantee health as a separate fundamental right in India. The issues for consideration are multifarious, the most important being- whether we have reached the level of economic and health systems development so as to make this a justiciable right-implying that its denial is an offense.